Numerical modeling of the plane-parallel motion of conical projectiles in the soil environment based on a local interaction model - Kotov, Vasiliy Leonidovich; Konstantinov, Aleksandr Yurievich (Computational Continuum Mechanics, 2014)
The paper considers the accuracy of a local interaction model applied to the solution of impact problems and the problems of the plane-parallel motion of conical bodies at an angle to the free surface of the soil-filled half space. The parameters of the local interaction model quadratic in speed are determined by solving the problem of expansion of a spherical cavity. The medium is considered to be an elastoplastic medium with linear pressure-volumetric strain and yield stress-pressure linear relationships. 3D modeling carried out using the obtained parameters of the model yields the force and kinematic characteristics of penetration of conical projectiles into the soil (resistance force, speed and trajectory of the motion of the center of mass, and rotation angles) under the action of surface friction. It has been found that the local interaction model quadratic in speed satisfactorily describes the inertial motion of a conical projectile that moves normally to the surface of the soil and thus can represent the initial stage of inclined indentation. However, when the projectiles enter the soil, an error in determining both the force and kinematic characteristics is somewhat greater compared to normal impact. According to the authors, this is caused by the errors introduced by presetting normal stress in the framework of the local interaction model and Coulomb’s law of friction law. The Coulomb friction leads to an increase in the maximum angle of rotation of the projectile compared with the calculations ignoring friction forces, and the local interaction model qualitatively describes this trend.